152 Malignant ureteric obstruction decompression: how much gain for how much pain? a systematic review of the literature. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Prentice, Joanna; Amer, Tarik; Aboumarzouk, Omar M
Abstract : Background: Over the last thirty years, the management of Malignant Ureteric Obstruction (MUO) has evolved from a single disciplinary decision to a multi-disciplinary approach. Careful consideration must be given to the risks and benefits of decompression of hydronephrosis for an individual patient. Though there is some recommendations within cancer specific guidelines, both the European Association of Urology and the American Urological Association guidelines recommend drainage or de-obstructing the urinary systems, there is a lack of consensus of opinion as well as strong evidence to support the decision process. Methodology: The review was conducted using Cochrane and PRISMA guidelines. Outcomes that were identified amongst patients undergoing treatment for MUO included prognosis, quality of life (QOL), complications, morbidity and prognostication tools. Results: The initial review found 169 papers. A total of 56 papers were included. Median survival was 6.4 months in the 50 papers that stated this outcome. The average reported complication rate was 41% with one fifth of patients never leaving hospital post procedure. Significant predictors to poor outcomes included low serum albumin, hyponatremia, the number of malignancy related events, and performance status of 2 or worse on the European cooperative cancer group. For those patients with 2 or more risk factors, median survival ranged from 1.7–2.6 months and 12-month survival ranged from 0%–12%. QOL using several measures ranged from 41–88%. Conclusion: In this post Montgomery era with the concept of the 'reasonable patient', can we continue to justify discussing decompression without stating the evidence-based risks from the emergent body of literature? We propose a multi-centre review of outcomes to enable evidence-based consultations for patients and their families.